Glass composition and sealing material
A lead-free glass composition with B2O3, TeO2, and MoO3, combined with refractory fillers, addresses the challenge of achieving low-temperature sealing with high weather resistance, suitable for electronic component sealing and crystal resonator packages.
Patent Information
- Application Number
- JP2020151020
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-09
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-09-09
AI Technical Summary
Existing lead-borate glass compositions used for sealing materials face challenges in achieving both low softening points and high weather resistance, necessitating a transition to lead-free alternatives that maintain these properties.
A glass composition comprising B2O3 (1-20%), TeO2 (30-80%), MoO3 (5-30%), and optional additives like Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, ZnO, TiO2, Al2O3, CuO, WO3, Fe2O3, P2O5, and Fe2O3, along with a sealing material containing 40-100% glass powder and 0-60% refractory filler powder, particularly Zr2W2O7(P2O4)2, to achieve low-temperature sealing with improved weather resistance.
The proposed glass composition and sealing material enable low-temperature sealing with enhanced weather resistance, suitable for applications such as crystal resonator packages and semiconductor integrated circuits, while avoiding lead content for environmental reasons.
Smart Images

Figure 0007616507000002 
Figure 0007616507000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass composition and a sealing material that have weather resistance and can be hermetically sealed at low temperatures. [Background technology]
[0002] Sealing materials are used in semiconductor integrated circuits, quartz crystal oscillators, metal members, flat panel displays, glass terminals for LEDs, etc. Sealing materials are required to have chemical durability and heat resistance, so glass-based sealing materials are used instead of resin-based adhesives. Sealing materials are also required to have properties such as mechanical strength, fluidity, and weather resistance. In particular, sealing electronic components equipped with elements that are sensitive to heat is required to have a sealing temperature as low as possible. Specifically, it is required that sealing can be performed at a temperature of 400°C or less. As glass that satisfies these properties, lead borate glass containing a large amount of PbO, which has a large effect of lowering the softening point, has been widely used (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 63-315536 [Patent Document 2] JP 2019-202921 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to reduce the environmental load, it is desirable to replace lead-borate glasses with lead-free glasses that do not contain PbO, and various lead-free glasses with low softening points have been developed.
[0005] However, in general, when the softening point of glass is low, the weather resistance tends to decrease. Therefore, it is not easy to achieve both a low softening point and high weather resistance. The CuO-TeO2-MoO3-based glass described in Patent Document 2 is a promising candidate to replace lead borate-based glass, and although it has good weather resistance, it cannot be said that its softening point is sufficiently low.
[0006] In view of the above, an object of the present invention is to provide a glass composition and a sealing material that have good weather resistance and can be sealed at low temperatures. [Means for solving the problem]
[0007] As a result of extensive research, the present inventors have found that the above problems can be solved by using a specific B2O3-TeO2-MoO3-based glass, and propose this as the present invention. That is, the glass composition of the present invention is characterized by containing, in mole percent, 1-20% B2O3, 30-80% TeO2, and 5-30% MoO3.
[0008] Furthermore, the glass composition of the present invention preferably has a Li2O+Na2O+K2O content of 0 to 30 mol %. Note that "A+B+C" refers to the total amount of component A, component B, and component C. For example, "Li2O+Na2O+K2O" refers to the total amount of Li2O, Na2O, and K2O.
[0009] In the glass composition of the present invention, the content of MgO+CaO+SrO+BaO+ZnO is preferably 0 to 30 mol %.
[0010] In addition, the glass composition of the present invention preferably contains TiO2+Al2O3 in an amount of 0 to 10 mol %.
[0011] Moreover, the glass composition of the present invention preferably contains, in mole percent, 0-30% CuO, 0-20% WO3, 50-10% P2O, and 0-10% Fe2O3.
[0012] The sealing material of the present invention preferably contains 40 to 100% by volume of glass powder made of the above glass composition and 0 to 60% by volume of a refractory filler powder.
[0013] In addition, in the sealing material of the present invention, the refractory filler powder is preferably substantially spherical. Here, the term "substantially spherical" does not mean only a perfect sphere, but means that the value obtained by dividing the shortest diameter passing through the center of gravity of the refractory filler powder by the longest diameter of the refractory filler powder is 0.5 or more, preferably 0.7 or more.
[0014] In the sealing material of the present invention, all or a part of the refractory filler powder is preferably Zr2WO4(PO4)2.
[0015] The sealing material of the present invention is preferably used for a quartz crystal resonator package.
[0016] The sealing material paste of the present invention preferably contains the above-mentioned sealing material and a vehicle. Effect of the Invention
[0017] The present invention can provide a glass composition and a sealing material that have good weather resistance and can be sealed at low temperatures. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a schematic diagram showing a measurement curve obtained by a macro-type differential thermal analyzer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The glass composition of the present invention contains, in mol %, 1-20% B2O3, 30-80% TeO2, and 5-30% MoO3 as a glass composition. The reasons for limiting the glass composition range as described above are as follows. In the explanation of the content of each component, "%" means "mol %" unless otherwise specified.
[0020] B2O3 is a component that forms a glass network. The content of B2O3 is 1 to 20%, preferably 2 to 15%, and more preferably 4 to 10%. If the content of B2O3 is too low, the weather resistance is likely to decrease. On the other hand, if the content of B2O3 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult and the glass is likely to undergo phase separation. Also, vitrification becomes difficult.
[0021] TeO2 is a component that forms a glass network and improves weather resistance. The content of TeO2 is 30 to 80%, preferably 40 to 70%, and more preferably 50 to 65%. If the content of TeO2 is too low, the glass becomes thermally unstable and is prone to devitrification during melting or firing. On the other hand, if the content of TeO2 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult and tending to cause the thermal expansion coefficient to become too high.
[0022] MoO3 is a component that forms a glass network. The content of MoO3 is 5 to 30%, preferably 7 to 27%, more preferably 10 to 25%, further preferably 12 to 22%, and particularly preferably 15 to 20%. If the content of MoO3 is too low, vitrification becomes difficult, and the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult. On the other hand, if the content of MoO3 is too high, the glass becomes thermally unstable, and the glass is easily devitrified during melting or firing, and the thermal expansion coefficient tends to become too high.
[0023] In addition to the above components, the following components may be incorporated.
[0024] Li2O, Na2O and K2O are components that lower the viscosity (softening point, etc.) of glass. The content of Li2O+Na2O+K2O is preferably 0 to 30%, more preferably 5 to 25%, and further preferably 10 to 20%. If the content of Li2O+Na2O+K2O is too small, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may become difficult. On the other hand, if the content of Li2O+Na2O+K2O is too large, the glass becomes thermally unstable and is easily devitrified during melting or firing. Also, the weather resistance is easily reduced and the thermal expansion coefficient tends to become too high.
[0025] Li2O is a component that significantly reduces the viscosity (softening point, etc.) of glass compared to Na2O and K2O. The content of Li2O is preferably 0 to 30%, more preferably 1 to 20%, further preferably 3 to 15%, and particularly preferably 5 to 13%. If the content of Li2O is too small, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may become difficult. On the other hand, if the content of Li2O is too large, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Also, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.
[0026] Na2O is a component that reduces the viscosity (softening point, etc.) of glass compared with K2O. The content of Na2O is preferably 0 to 20%, more preferably 0 to 15%, further preferably 0 to 10%, and particularly preferably 1 to 7%. If the content of Na2O is too small, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may become difficult. On the other hand, if the content of Na2O is too large, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Also, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.
[0027] K2O is a component that reduces the viscosity (softening point, etc.) of glass. The content of K2O is preferably 0 to 30%, more preferably 1 to 20%, further preferably 3 to 15%, and particularly preferably 5 to 13%. If the content of K2O is too low, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may become difficult. On the other hand, if the content of K2O is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Also, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.
[0028] The molar ratio Li2O / K2O is preferably 0.3 to 5, more preferably 0.4 to 4, 0.5 to 3, further preferably 0.6 to 2, and particularly preferably 0.7 to 1.5, in order to lower the softening point by the alkali mixing effect. If the molar ratio Li2O / K2O is outside the above range, the glass becomes thermally unstable and may easily devitrify during melting or firing. Note that "Li2O / K2O" refers to the value obtained by dividing the content of Li2O by the content of K2O.
[0029] MgO, CaO, SrO, BaO and ZnO are components that broaden the vitrification range and improve weather resistance. MgO+CaO+SrO+BaO+ZnO is preferably 1 to 30%, more preferably 3 to 20%, and even more preferably 5 to 15%. If the content of MgO+CaO+SrO+BaO+ZnO is too small, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may become difficult. On the other hand, if the content of MgO+CaO+SrO+BaO+ZnO is too large, the glass becomes thermally unstable and is easily devitrified during melting or firing. Also, the weather resistance is easily reduced and the thermal expansion coefficient tends to become too high.
[0030] MgO is a component that broadens the vitrification range and improves weather resistance. The content of MgO is preferably 0 to 25%, more preferably 0 to 20%, further preferably 0 to 10%, and particularly preferably 1 to 7%. If the content of MgO is low, vitrification may be difficult. Furthermore, the viscosity (softening point, etc.) of the glass may increase, making sealing at low temperatures difficult. On the other hand, if the content of MgO is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Furthermore, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.
[0031] CaO is a component that broadens the vitrification range and improves weather resistance. The CaO content is preferably 0 to 25%, more preferably 0 to 20%, further preferably 0 to 10%, and particularly preferably 1 to 7%. If the CaO content is low, vitrification may be difficult. Furthermore, the viscosity (softening point, etc.) of the glass may increase, making sealing at low temperatures difficult. On the other hand, if the CaO content is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Furthermore, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.
[0032] SrO is a component that broadens the vitrification range and improves weather resistance. The content of SrO is preferably 0 to 25%, more preferably 0 to 20%, further preferably 0 to 10%, and particularly preferably 1 to 7%. If the content of SrO is low, vitrification may be difficult. Furthermore, the viscosity (softening point, etc.) of the glass may increase, making sealing at low temperatures difficult. On the other hand, if the content of SrO is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Furthermore, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.
[0033] BaO is a component that broadens the vitrification range and improves weather resistance. The content of BaO is preferably 0 to 25%, more preferably 0 to 20%, further preferably 0 to 10%, and particularly preferably 1 to 7%. If the content of BaO is low, vitrification may be difficult. Furthermore, the viscosity (softening point, etc.) of the glass may increase, making sealing at low temperatures difficult. On the other hand, if the content of BaO is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Furthermore, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.
[0034] ZnO is a component that broadens the vitrification range and improves weather resistance. The content of ZnO is preferably 0 to 25%, more preferably 0 to 20%, further preferably 0 to 10%, and particularly preferably 1 to 7%. If the content of ZnO is too low, vitrification becomes difficult. In addition, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult. On the other hand, if the content of ZnO is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. In addition, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.
[0035] TiO2 and Al2O3 are components that improve weather resistance. The content of TiO2+Al2O3 is preferably 0 to 10%, more preferably 0.1 to 8%, further preferably 1 to 6%, and particularly preferably 2 to 5%. If the content of TiO2+Al2O3 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.
[0036] Al2O3 is a component that improves weather resistance. The content of Al2O3 is preferably 0 to 10%, more preferably 0.1 to 8%, further preferably 1 to 6%, and particularly preferably 2 to 5%. If the content of Al2O3 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.
[0037] TiO2 is a component that improves weather resistance. The content of TiO2 is preferably 0 to 8%, more preferably 0.1 to 6%, further preferably 1 to 5%, and particularly preferably 2 to 4%. If the content of TiO2 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.
[0038] CuO is a component that reduces the viscosity (softening point, etc.) of glass and also reduces the thermal expansion coefficient. In addition, when sealing a metal, it is a component that increases the adhesive strength between glass and metal. Although the mechanism for increasing the adhesive strength is unclear at present, it is considered that Cu atoms have high diffusivity, and therefore Cu atoms diffuse from the surface layer of the metal toward the inside, making it easier for glass and metal to be integrated. There is no particular restriction on the type of metal to be sealed, and examples include iron, iron alloy, nickel, nickel alloy, copper, copper alloy, aluminum, and aluminum alloy. The content of CuO is preferably 0 to 30%, more preferably 0 to 10%, even more preferably 0.1 to 5%, and particularly preferably 0.5 to 3%. In addition, the content of CuO when sealing a metal is preferably 1 to 30%, more preferably 1 to 20%, even more preferably 3 to 15%, and particularly preferably 5 to 10%. If the CuO content is too high, the glass becomes thermally unstable, and metallic Cu may precipitate on the glass surface during the sealing process, adversely affecting the sealing strength and electrical properties. In addition, the glass becomes easily devitrified during melting or firing.
[0039] WO3 is a component that reduces the thermal expansion coefficient. The content of WO3 is preferably 0 to 20%, 0.1 to 10%, and particularly preferably 1 to 5%. If the content of WO3 is too high, the glass becomes thermally unstable, the glass becomes more likely to devitrify during melting or firing, and the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.
[0040] P2O5 is a component that forms a glass network and thermally stabilizes glass. The content of P2O5 is preferably 0 to 10%, more preferably 0.1 to 5%, further preferably 0.2 to 2%, and particularly preferably 0.5 to 1%. If the content of P2O5 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult and weather resistance easily decreases.
[0041] Fe2O3 is a component that enhances the reactivity with the material to be sealed. The content of Fe2O3 is preferably 0 to 25%, more preferably 0 to 20%, further preferably 0 to 10%, and particularly preferably 1 to 7%. If the content of Fe2O3 is too high, vitrification becomes difficult and the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.
[0042] Ag2O is a component that reduces the viscosity (softening point, etc.) of glass. The content of Ag2O is preferably 0 to 10%, more preferably 0 to 5%, further preferably 0 to 3%, and particularly preferably 0 to 2%. If the content of Ag2O is too high, the glass becomes thermally unstable and is likely to devitrify during melting or firing. In addition, there is a risk that metallic Ag will precipitate from the glass depending on the firing atmosphere.
[0043] AgI is a component that reduces the viscosity (softening point, etc.) of glass. The content of AgI is preferably 0 to 10%, more preferably 0 to 5%, further preferably 0 to 2%, and particularly preferably 0 to 1%. If the content of AgI is too high, the thermal expansion coefficient tends to be too high.
[0044] Nb2O5 is a component that thermally stabilizes glass and enhances weather resistance. The content of Nb2O5 is preferably 0 to 10%, more preferably 0 to 5%, further preferably 0 to 2%, and particularly preferably 0 to 1%. If the content of Nb2O5 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.
[0045] V2O5 is a component that forms a glass network and reduces the viscosity (softening point, etc.) of the glass. The content of V2O5 is preferably 0 to 10%, more preferably 0 to 5%, even more preferably 0 to 3%, and still more preferably 0 to 2%. If the content of V2O5 is too high, the glass becomes thermally unstable, and the glass is likely to devitrify during melting or firing, and the weather resistance is likely to decrease.
[0046] Ga2O3 is a component that thermally stabilizes glass and also enhances weather resistance, but is very expensive, so its content is preferably less than 0.01%.
[0047] GeO2, Nb2O5, CeO2, Sb2O3, and La2O3 are components that thermally stabilize glass and suppress devitrification, and each can be added up to less than 5%. If the content of these components is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing.
[0048] For environmental reasons, the glass composition of the present invention preferably contains substantially no PbO. Here, "substantially no PbO" refers to the case where the PbO content in the glass composition is less than 0.1%.
[0049] The sealing material of the present invention contains glass powder made of the above glass composition. The sealing material of the present invention may contain a refractory filler powder in order to improve mechanical strength or adjust the thermal expansion coefficient. The mixing ratio is preferably 40 to 100 volume % of glass powder and 0 to 60 volume % of refractory filler powder, more preferably 50 to 99 volume % of glass powder and 1 to 50 volume % of refractory filler powder, still more preferably 60 to 95 volume % of glass powder and 5 to 40 volume % of refractory filler powder, and particularly preferably 70 to 90 volume % of glass powder and 10 to 30 volume % of refractory filler powder. If the content of the refractory filler powder is too high, the ratio of the glass powder becomes relatively small, making it difficult to ensure the desired fluidity.
[0050] The refractory filler powder preferably contains Zr2WO4(PO4)2, which is unlikely to react with the glass powder according to the present invention and has the property of significantly lowering the thermal expansion coefficient of the sealing material.
[0051] In addition, the sealing material of the present invention may use a refractory filler powder other than Zr2WO4(PO4)2 as the refractory filler powder. Other refractory filler powders include NbZr(PO4)3, Zr2MoO4(PO4)2, Hf2WO4(PO4)2, Hf2MoO4(PO4)2, zirconium phosphate, zircon, zirconia, tin oxide, aluminum titanate, quartz, β-spodumene, mullite, titania, quartz glass, β-eucryptite, β-quartz, willemite, cordierite, Sr 0.5 Powders made of Zr2(PO4)3 and the like can be used alone or in combination of two or more kinds.
[0052] The refractory filler powder is preferably substantially spherical. In this way, when the glass powder softens, the fluidity of the glass powder is less likely to be hindered by the refractory filler powder, and as a result, the fluidity of the sealing material is improved. In addition, a smooth glaze layer is easily obtained. Furthermore, even if a part of the refractory filler powder is exposed on the surface of the glaze layer, the stress of this part is dispersed because the refractory filler powder is substantially spherical. As a result, even if the sealed object is in contact with the glaze layer during sealing, undue stress is less likely to be applied to the sealed object, and airtightness is easily ensured.
[0053] Average particle size of refractory filler powder D 50 The average particle diameter D is preferably 0.2 to 20 μm, and more preferably 2 to 15 μm. 50 If the average particle diameter D is too large, the sealing layer tends to become thick. 50 If the value is too small, the refractory filler powder will dissolve into the glass during sealing, making the glass prone to devitrification.
[0054] In the sealing material of the present invention, the softening point is preferably 350° C. or less, and particularly preferably 340° C. or less. If the softening point is too high, the viscosity of the glass increases, and the sealing temperature rises, which may cause deterioration of the element due to the heat during sealing. The lower limit of the softening point is not particularly limited, but is practically 180° C. or more. Here, the "softening point" refers to the average particle diameter D 50 The softening point is measured by a macro-type differential thermal analyzer using a sealing material having a thickness of 0.5 to 20 μm as a measurement sample. The measurement conditions are as follows: the measurement is started at room temperature, and the heating rate is 10°C / min. The softening point measured by the macro-type differential thermal analyzer is the temperature (Ts) of the fourth bending point in the measurement curve shown in FIG. 1.
[0055] In the sealing material of the present invention, the thermal expansion coefficient in the temperature range of 30 to 150° C. is preferably 20×10 -7 / ℃~200×10 -7 / °C, more preferably 30×10 -7 / ℃~160×10 -7 / °C, more preferably 40×10 -7 / ℃~140×10 -7 / °C, and especially preferably 50×10 -7 / ℃~120×10 -7 If the thermal expansion coefficient is outside the above range, the difference in thermal expansion with the material to be sealed makes the sealed portion prone to damage during or after sealing.
[0056] Next, an example of a method for producing the glass powder and the sealing material according to the present invention and a method for using the same will be described.
[0057] First, raw material powders prepared to obtain a desired glass composition are melted at 800 to 1000°C for 1 to 2 hours until a homogeneous glass is obtained. Next, the obtained molten glass is formed into a film or the like, and then crushed and classified to produce glass powder. The average particle diameter D of the glass powder is 1.0 mm. 50 The particle size is preferably about 1 to 20 μm. If necessary, various fire-resistant filler powders are added to the glass powder and mixed to prepare a sealing material.
[0058] Next, a vehicle is added to the sealing material and kneaded to prepare a sealing material paste. The vehicle mainly consists of an organic solvent and a resin, and the resin is added to adjust the viscosity of the paste. If necessary, a surfactant, a thickener, etc. can also be added.
[0059] The organic solvent is preferably one that has a low boiling point (for example, a boiling point of 300° C. or less), leaves little residue after firing, and does not alter the glass, and the content is preferably 10 to 40% by mass. As the organic solvent, it is preferable to use propylene carbonate, toluene, N,N'-dimethylformamide (DMF), 1,3-dimethyl-2-imidazolidinone (DMI), dimethyl carbonate, butyl carbitol acetate (BCA), isoamyl acetate, dimethyl sulfoxide, acetone, methyl ethyl ketone, etc. Furthermore, it is more preferable to use a higher alcohol as the organic solvent. Since higher alcohols themselves have viscosity, they can be made into a paste without adding a resin to the vehicle. Furthermore, pentanediol and its derivatives, specifically diethylpentanediol (CH 20 O2) also has excellent viscosity and can be used as a solvent.
[0060] The resin preferably has a low decomposition temperature, leaves little residue after firing, and is less likely to deteriorate the glass, and the content is preferably 0.1 to 20% by mass. As the resin, it is preferable to use nitrocellulose, polyethylene glycol derivatives, polyethylene carbonate, acrylic esters (acrylic resins), etc.
[0061] Next, the sealing material paste is applied to the sealing portions of the objects to be sealed, which are made of metal, ceramic, or glass, using an applicator such as a dispenser or a screen printer, dried, and glazed at 300 to 350° C. Thereafter, another object to be sealed is brought into contact with the sealing material paste and heat-treated at 350 to 400° C., whereby the glass powder softens and flows, and the two are sealed together.
[0062] The glass powder according to the present invention can be used for purposes other than sealing, such as coating and filling, etc. Also, it can be used in a form other than a paste, specifically, in a form such as a powder, a green sheet, or a tablet (a powder material sintered into a predetermined shape). EXAMPLES
[0063] The present invention will be described in detail with reference to examples. Table 1 shows examples of the present invention (samples Nos. 1 to 10) and comparative examples (samples Nos. 11 and 12).
[0064] [Table 1]
[0065] First, raw material powders prepared to obtain the glass composition shown in the table were placed in a platinum crucible and melted in air at 800 to 1000°C for 1 to 2 hours. The molten glass was then formed into a film using a water-cooled roller, and the film-like glass was crushed in a ball mill and passed through a sieve with 75 μm openings to obtain the average particle diameter D 50 The glass powder obtained was about 10 μm in size.
[0066] Thereafter, the obtained glass powder and the refractory filler powder were mixed as shown in the table to obtain a mixed powder.
[0067] The refractory filler powder used was roughly spherical Zr2WO4(PO4)2 (referred to as ZWP in the table) and NbZr(PO4)3 (referred to as NZP in the table). The average particle diameter D 50 was about 10 μm.
[0068] Samples Nos. 1 to 12 were evaluated for glass transition point, thermal expansion coefficient, softening point, fluidity, and weather resistance.
[0069] The glass transition point and the thermal expansion coefficient in the temperature range of 30 to 150°C were evaluated as follows. First, the mixed powder was placed in a rod-shaped mold and press-molded, and then sintered at 380°C for 10 minutes on an alumina substrate coated with a release agent. The sintered body was then processed into a specified shape and measured with a TMA device.
[0070] The softening point was measured by a macro-type differential thermal analyzer, and the fourth bending point was taken as the softening point. The measurement was performed in air, the temperature was increased at a rate of 10° C. / min, and the measurement was started from room temperature.
[0071] The flowability was evaluated as follows: A mass of the mixed powder corresponding to the composite density was placed in a mold with a diameter of 20 mm, press molded, and then fired on a glass substrate at 380°C for 10 minutes. Fired bodies with a flow diameter of 19 mm or more were rated as "○", and those with a flow diameter of less than 19 mm were rated as "×".
[0072] Weather resistance was evaluated by an accelerated deterioration test using the PCT (Pressure Cooker Test). Specifically, the fired bodies prepared above were kept in an environment of 121°C, 2 atm, and 100% relative humidity for 24 hours, and then visually observed. Those that had no precipitates on the surface of the fired bodies were rated as "good", and those that did not were rated as "bad".
[0073] As is clear from the table, samples No. 1 to No. 10 were evaluated as good in terms of fluidity and weather resistance. On the other hand, sample No. 11 did not vitrify because the content of B2O3 in the glass composition was high. Sample No. 12 had poor weather resistance because it did not contain B2O3 in the glass composition. [Industrial Applicability]
[0074] The glass composition of the present invention is suitable for sealing quartz crystal oscillator packages, and is also suitable for sealing airtight packages of semiconductor integrated circuits, flat panel displays, glass terminals for LEDs, aluminum nitride substrates, etc. It can also be used as a sealing material for metals.
Claims
1. The glass composition is, in mole percent, B 2 O 3 1-20%, TeO 2 40-80%, MoO 3 A sealing material comprising: 40 to 100 volume % of glass powder made of a glass composition containing 5 to 30% of LiO, 10 to 30% of Li 2 O+Na 2 O+K 2 O, and substantially no PbO; and 0 to 60 volume % of a fire-resistant filler powder.
2. 2. The sealing material according to claim 1, wherein the content of MgO+CaO+SrO+BaO+ZnO in the glass composition is 0 to 30 mol %.
3. TiO in the glass composition 2 +Al 2 O 3 The sealing material according to claim 1 or 2, characterized in that the content of is 0 to 10 mol %.
4. The glass composition is composed of, in mole percent, CuO 0 to 30%, WO 3 0-20%, P 2 O 5 0-10%, Fe 2 O 3 4. The sealing material according to claim 1, comprising 0 to 10% by weight of the polyvinyl chloride.
5. 5. The sealing material according to claim 1, wherein the refractory filler powder is substantially spherical.
6. The refractory filler powder is entirely or partially Zr 2 WO 4 (P.O. 4 ) 2 The sealing material according to any one of claims 1 to 5, characterized in that
7. 7. The sealing material according to claim 1, which is used for a quartz crystal oscillator package.
8. A sealing material paste comprising the sealing material according to any one of claims 1 to 7 and a vehicle.
Citation Information
Patent Citations
Frit for low-temperature sealing
JP1988315536A
Sealing glass
JP1991218943A
Low-temperature seal member and method for manufacturing the same
JP2018152385A
Glass composition and sealing material
JP2019202921A